2019
DOI: 10.1002/dta.2702
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 5α‐reductase inhibitors by UPLC–MS/MS: Application to the definition of the excretion profile of dutasteride in urine

Abstract: An analytical procedure based on ultra‐performance liquid chromatography‐mass spectrometry was developed to screen and to confirm dutasteride and its metabolites in human urine. Sample preparation included an enzymatic hydrolysis followed by solid‐phase extraction using the strong cation exchange cartridges OASIS® MCX. The chromatographic separation was carried out on C18 column, employing as mobile phases ultra purified water and acetonitrile, both containing 0.1% formic acid. Detection was achieved using a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Sample preparation was performed following the validated procedure used at the WADA‐accredited laboratory of Rome, for the detection of the EAAS in human urine 28,38 . Briefly, 0.75 ml of phosphate buffer (0.8 M, pH 7.4), 50 μl of internal standards mixture (constituted by a pool of deuterated steroids: 100 ng/ml of T‐d3, 25 ng/ml of E‐d3, 50 ng/ml of 5αAdiol‐d3 and 5βAdiol‐d5, and 2000 ng/ml of AG‐d4 and Etio‐d5), and 30 μl of β‐glucuronidase from E. coli were added to 2 ml of urine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample preparation was performed following the validated procedure used at the WADA‐accredited laboratory of Rome, for the detection of the EAAS in human urine 28,38 . Briefly, 0.75 ml of phosphate buffer (0.8 M, pH 7.4), 50 μl of internal standards mixture (constituted by a pool of deuterated steroids: 100 ng/ml of T‐d3, 25 ng/ml of E‐d3, 50 ng/ml of 5αAdiol‐d3 and 5βAdiol‐d5, and 2000 ng/ml of AG‐d4 and Etio‐d5), and 30 μl of β‐glucuronidase from E. coli were added to 2 ml of urine.…”
Section: Methodsmentioning
confidence: 99%
“…In the doping control field, the alteration of the natural fluctuation of several endogenous steroids (currently: testosterone [T], epitestosterone [E], androsterone [A], etiocholanolone [Etio], 5α‐androstane‐3α,17β‐diol [5αAdiol], 5β‐androstane‐3α,17β‐diol [5βAdiol], T/E, A/T, A/Etio, 5αAdiol/5βAdiol, and 5αAdiol/E) is considered, since the 1980s, a screening index of the intake of testosterone‐related compounds 19 ; consequently, any natural or synthetic substance capable of affecting the physiological levels of the target endogenous steroids might lead to a wrong interpretation of the results. For the above reason in 2016, antifungals were included by the World Anti‐Doping Agency (WADA) in the Technical Document TDEAAS “Endogenous Anabolic Androgenic Steroids—Measurement and Reporting,” 20,21 together with other exogenous compounds (e.g., 5α‐reductase inhibitors, alcohol, and bacterial contamination) or physiopathologic confounding factors (e.g., pregnancy, hormonal dysfunction, and genetic polymorphism) 22–29 . The WADA TDEAAS aims at harmonizing the approaches to the measurement and reporting of endogenous anabolic androgenic steroids (EAAS) in urine samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of dutasteride into routine doping control analytical assays has been a major challenge due to the extensive metabolism and the predominantly fecal elimination route of the substance. By means of enzymatic hydrolysis, mixed cation‐exchange SPE, and subsequent LC‐MS/MS analysis, the sensitive detection of diagnostic metabolites of dutasteride was accomplished by Mazzarino et al, facilitating the monitoring of dutasteride use to ensure the quality of the ABP interpretations 71 . The instrument used was composed of an LC equipped with a C‐18 analytical column (150 × 2.1 mm, 2.7 μm particle size) employing gradient elution with 0.1% formic acid (solvent A) and acetonitrile (containing 0.1% formic acid).…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Dutasteride especially has been shown to be a challenging representative for doping controls due to its predominantly fecal elimination and comprehensive metabolism. By means of controlled administration studies, new target analytes were identified with 4′‐ and 6‐hydroxylated dutasteride, facilitating the routine detection of dutasteride administrations . In another study, the influence of an Ironman competition on the hematological module of the athlete biological passport and, consequently, on potential atypical passport findings was investigated, outlining a considerable effect of athletic stress to be factored in to athlete biological passport profile interpretations .…”
mentioning
confidence: 99%